Auditory Perception Modes and Effects on Meditation: Case Study of Thai Cooking Sounds - Pasupa, Martsamrit; Joneurairatana, Eakachat; Simatrung , Sone (วารสารสันติศึกษาปริทรรศน์ มจร, 2023)
Meditation is a method that effectively helps relieve stress. However, a distracted mind can hinder the meditation practice. Therefore, sounds play a significant role in human behavior, and each individual’s perception can create different feelings or environments. So far, there are no fixed rules or guidelines on such creations or sound selection to support meditation. With this in mind, the aim of this research is 1) to study the significance of sound in meditation, 2) to analyze the factors of sound in meditation, 3) to present efficient sound modes for meditation using the components of Thai cooking sounds case study, and 4) to provide efficient meditation sound modes for testing and qualitative assessment by collecting data of the Top Ten Thai food as ranked by BBC Good Food. The research findings revealed: 1) Auditory perception modes during meditation differed from regular auditory perception, which is primarily supported by visual data. During meditation, practitioners close their eyes to eliminate data or stimuli; however, auditory data cannot be completely eliminated. 2) Sounds also aid meditators in visualizing more easily, making them a key factor in meditation. 3) Regarding efficient sound modes for meditation, the analysis of twenty sound samples showed that the most effective ones contain speeds or rhythms between 50 - 60 bpm, with keynote sound components below 200hz. It is advisable to avoid sound bandwidths between 300 – 1000 Hz, as sounds in this range are well perceived and can stimulate complex data processing and thinking, which should be essentially avoided. 4) The effects of the sound modes which were tested sound components of Thai cooking, and qualitative assessment through sample tests confirmed that these sounds can be used and support meditation.